Can vitamin C affect the KBrO3 induced oxidative stress on left ventricular myocardium of adult male albino rats? A histological and immunohistochemical study. Issue 3 (September 2015) - El-Deeb, Mohammad E.E.; Abd-El-Hafez, Amal A.A.
Abstract: Potassium bromate (KBrO3 ) cardiotoxicity is not widely recognized, in spite of its well known oxidative cell and tissue damage. The wide exposure to KBrO3 in food and water necessitates finding of a simple and available antidote for its hazards like vitamin C. There are growing evidences that the regulation of redox reactions in cells is intimately tied to the levels of antioxidants. As the heart is highly vulnerable for oxidative damage, left ventricle muscle was the spotlight of our study. For this purpose 20 adult male albino rats were categorized into four groups (five rats each). Group 1 served as control; group 2 received 30 mg/kg/day vitamin C for 4 weeks. Group 3 was injected intraperitoneally with KBrO3 20 mg/kg/dose twice weekly for 4 weeks, and group 4 received both vitamin C and KBrO3 in the same scheme. Heart specimens were processed for various histological examinations. Sections from KBrO3 treated animals showed focal disruption of cardiac myocytes, deeply stained nuclei and dilated congested blood vessels. Ultrastructurally, irregular indented nuclei, focal lysis of the myofibrils and swelling of mitochondria were also observed. In contrast, minimal changes were observed in rats treated concomitantly with both vitamin C and KBrO3 . Caspase 3 immunohistochemical reaction was nonsignificantly increased in group 3 cardiomyocytes. Semiquantitative morphological mitochondrial scoring and statistical analyses revealed significant changes between the studied groups. Finally, KBrO3 induced structural changes in rat cardiac muscle could be ameliorated by concomitant treatment with vitamin C.